PENGARUH BUAH DAN SAYUR TERHADAP KEBUGARAN PADA LANSIA - Anita Chandra Hidayat (2021)
As people get older, the elderly have health vulnerabilities so they need special protection and attention. According to 2019 Susenas data, the elderly population (elderly) in DKI Jakarta is dominated by the category of young elderly (60 - 69 years) by 71%. The fitness condition of the elderly is an indicator that can be used to determine the health level of the elderly. To achieve health, one of them is having a healthy lifestyle and consuming adequate nutrition, for example by consuming fruits and vegetables. The purpose of this literature study was to determine the relationship between fruits and vegetables on fitness in the elderly. The research design used was a systematic literature review, with the PICO method (Population, Intervention, Comparison, Outcome) with the keywords elderly, healthy, fruit and vegetables. The sample journals that were studied were 5 journals. The results of this study indicate that one way to maintain fitness in the elderly is to do physical activity and maintain a good diet, one of which is to eat fruits and vegetables that are rich in antioxidants. This is because there is one mechanism by inhibiting oxidant enzymes and reducing the production of cell reactive oxygen species. Keywords: elderly, fruit and vegetables, fitness